Temporal resolution in transmission electron microscopy using a photoemission electron source. (12th December 2022) - Kuwahara, Makoto; Agemura, Toshihide
Abstract: Temporal resolution in transmission electron microscopy (TEM) has progressed to the sub-picosecond level with the stroboscopic method using a photoemission mechanism with an ultrafast laser for the electron gun. Time-resolved TEM in conjunction with a photocathode (PC)-type electron source pumped by a pulsed laser has been actively developed to exceed sub-nanosecond time resolution. Here, we provide an overview of the trends in this field and discuss the measurement targets that can be obtained by time-resolved measurements. Furthermore, we consider the types and characteristics of PC materials and their related physical quantities for evaluation of electron beam properties. Experimental results obtained by time-resolved TEM using a semiconductor PC that has a surface with a negative electron affinity are presented, and application results based on quantum mechanics are given. We also describe new techniques for improving the time resolution and new applications of pulsed electron beams in electron microscopy and discuss the measurement targets that are expected for time-resolved electron microscopy.